1999
DOI: 10.1093/rheumatology/38.5.407
|View full text |Cite
|
Sign up to set email alerts
|

Serum MMP-3 in rheumatoid arthritis: correlation with systemic inflammation but not with erosive status.

Abstract: Serum MMP-3 is not an independent marker of joint damage, but is correlated with systemic inflammation. Its precise role in joint damage in RA remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 1 publication
9
34
0
5
Order By: Relevance
“…This lends indirect support to the notion that destruction and inflammation are distinct processes that do not necessarily occur together but may, as has been previously suggested, become "uncoupled" (48). Some authors suggest that levels of MMP-3 simply respond as markers of inflammation, rather than as markers of joint destruction (49)(50)(51). However, the results of our multivariate modeling indicate that MMP-3 levels are intimately related to destructive processes that result in radiographic progression.…”
Section: Young-min Et Alsupporting
confidence: 56%
“…This lends indirect support to the notion that destruction and inflammation are distinct processes that do not necessarily occur together but may, as has been previously suggested, become "uncoupled" (48). Some authors suggest that levels of MMP-3 simply respond as markers of inflammation, rather than as markers of joint destruction (49)(50)(51). However, the results of our multivariate modeling indicate that MMP-3 levels are intimately related to destructive processes that result in radiographic progression.…”
Section: Young-min Et Alsupporting
confidence: 56%
“…Association of the MMP-1-MMP-3 loci with disease activity Previous studies have shown significant correlations of MMP-1, and particularly MMP-3 serum levels with levels of inflammation in RA. 7,[9][10][11][13][14][15] In this study, we found significant correlations of MMP-1 and MMP-3 with the level of disease activity (DAS28 at baseline Figure 2 Relationship between MMP genotypes and circulating levels of MMPs. Panels (a-d) show serum levels of MMP-1 in patients with different genotypes of rs1799750, rs495366, rs679620 and rs3025058, respectively.…”
Section: Association Of Mmp-1-mmp-3 Loci With Circulating Levels Of Mmpsmentioning
confidence: 72%
“…Elevated levels of MMP-1 and -3 have been observed in patients with RA in both serum and synovial fluid, and are strongly associated with inflammation and joint destruction. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The genes for MMP-1 and -3 are both located on the long arm of chromosome 11, in a cluster together with seven other MMP members including MMP-7, -8, -10, -12 and -13. In recent years, functionally relevant and phenotype associated polymorphisms have been detected across the region of both genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] MMP-3 is not an independent marker of joint disease in rheumatoid arthritis, but is correlated with systemic inflammation. 26 Inflammatory cytokines (such as interleukin-1, interleukin-6, tumor necrosis factor-␣) are potent inducers of some MMPs including MMP-1, -3, and -9, and they may increase transcription by as much as 100-fold. [27][28][29] The production and secretion of MMP-2 and -3 can be stimulated by the acute-phase protein SAA.…”
Section: Discussionmentioning
confidence: 99%